Investigation Of The Influence Of The Characteristics Of Dynamic Action On The Amount Of Deflections Of Non-Rigid Road Pavements - A.A. Mukhidov; B.D. Salimova (International Scientific and Current Research Conferences, 2020)
This article presents the primary results of the study, a comparison of the results and their influence on the characteristics of the dynamic impact on the amount of deflections of non-rigid road pavements.